How a simple adaptive foraging strategy can lead to emergent home ranges and increased food intake - Nabe-Nielsen, J.; Tougaard, J.; Teilmann, J.; Lucke, Klaus; Forchhammer, M. (Wiley-Blackwell Publishing, Inc., 2013)
Animalsoften alternate between searching for food locally and moving over larger distances depending on the amount offood they find. This ability to switch between movement modes can have large implications on the fate of individuals andpopulations, and a mechanism that allows animals to find the optimal balance between alternative movement strategies istherefore selectively advantageous. Recent theory suggests that animals are capable of switching movement mode dependingon heterogeneities in the landscape, and that different modes may predominate at different temporal scales. Here wedevelop a conceptual model that enables animals to use either an area-concentrated food search behavior or undirectedrandom movements. The model builds on the animals’ ability to remember the profitability and location of previouslyvisited areas. In contrast to classical optimal foraging models, our model does not assume food to be distributed inlarge, well-defined patches, and our focus is on animal movement rather than on how animals choose between foragingpatches with known locations and value. After parameterizing the fine-scale movements to resemble those of the harborporpoise Phocoena phocoena we investigate whether the model is capable of producing emergent home ranges and usepattern-oriented modeling to evaluate whether it can reproduce the large-scale movement patterns observed for porpoisesin nature. Finally we investigate whether the model enables animals to forage optimally. We found that the model wasindeed able to produce either stable home ranges or movement patterns that resembled those of real porpoises. It enabledanimals to maximize their food intake when fine-tuning the memory parameters that controlled the relative contributionof area concentrated and random movements.